Digital mapping of corrosion risk in coastal urban areas using remote sensing and structural condition assessment: Case study in Cyprus - Neocleous, Kyriacos; Christofe, Andreas; Agapiou, Athos; Evagorou, Evagoras G.; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2016)
Atmospheric corrosion is one of the main factors leading to performance deterioration of reinforced concrete buildings; and, hence, periodic structural condition monitoring is required to assess and repair the adverse effects of corrosion. However, this can become a cumbersome and expensive task to undertake for large populations of buildings, scattered in large urban areas. To optimize the use of available resources, appropriate tools are required for the assessment of corrosion risk of reinforced concrete construction. This paper proposes a framework for the production of digital corrosion risk maps for urban areas; Cyprus was used as a case study. This framework explored multi-temporal satellite remote sensing data from the Landsat sensors as well as corrosion risk factors derived from the results of a recently completed research project, entitled "STEELCOR". This framework was used to develop two corrosion risk scenarios within Geographical Information Systems, and to produce corrosion risk maps for three coastal cities of Cyprus. The thematic maps indicated that, for slight corrosion damage, the distance of reinforced concrete buildings from the coast was more influential than the building age. While, for significant corrosion damage, the maps indicated that the age of RC buildings was more influential than the distance from the coast.
Keywords: classification; GIS; Landsat; non-destructive testing; reinforced concrete; risk area; satellite remote sensing; simplified damage index; steel corrosion